2014
DOI: 10.7220/2335-8777.5.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Bedarbiai vyrai, geras gyvenimas ir socialinė atskirtis

Abstract: ĮvadasKas nutinka, kada tai, ko trokšti, pasirodo vis labiau nepasiekiama? Kas įvyksta, kai prisirišimas prie teisingo ir visuotinai pripažinto gyvenimo naratyvo žlunga ir kai tavo kasdienės pastangos jį įgyvendinti tėra tik beviltiš-ko optimizmo tęsinys? Pastarasis terminas "beviltiškas optimizmas" skamba kaip oksimoronas, tačiau jis yra nuoroda į tai, ką išgyvena kasdienybėje šio straipsnio veikėjai -bedarbiai vyrai. Neviltis ir optimizmas, džiaugsmas ir gėda, gyvenimo gerovė ir socialinės atskirties baimė -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
0
0
0
2
Order By: Relevance
“…In Lithuania, studies that directly address social segregation and its spatial dimension have only recently started to appear. The studies by Krupickaitė (2014), Žilys (2013) and Tereškinas et al (2013) were survey-based and the spatial dimension rather limited as a result. Research by Marcińczak et al (2015) was based on the 2001 census data at the level of census tracts.…”
Section: Social Segregationmentioning
confidence: 99%
See 1 more Smart Citation
“…In Lithuania, studies that directly address social segregation and its spatial dimension have only recently started to appear. The studies by Krupickaitė (2014), Žilys (2013) and Tereškinas et al (2013) were survey-based and the spatial dimension rather limited as a result. Research by Marcińczak et al (2015) was based on the 2001 census data at the level of census tracts.…”
Section: Social Segregationmentioning
confidence: 99%
“…Individuallevel data is the most suitable for migration studies; however, until now individuallevel census data was not available to socio-spatial researchers. Thirdly, research on social segregation is also scarce in Lithuania (the rare examples are Krupickaitė, 2014;Marcińczak et al, 2015;Tereškinas et al, 2013;Žilys, 2013). There are no previous studies investigating how the local spatial dimensions of social inequality have changed over time.…”
Section: Social Segregationmentioning
confidence: 99%
“…The combined effects of major political, economic and social transitions have resulted in a large-scale socio-spatial transformation in the CEE countries since the early 1990s (Brade et al, 2009;Marcińczak, 2012;Musil, 1993;Sýkora, 1999;Sýkora & Bouzarovski, 2012;Ubarevičienė et al, 2011). Research that directly addresses issues of housing and socio-economic segregation in Lithuania has only been carried out recently (Krupickaitė, 2014;Tereškinas, Žilys, & Indiliūnaitė, 2013;Žilys, 2013). The survey-based study of Krupickaitė (2014) showed that most of the suburban residents have a higher socio-economic status (in terms of income and education).…”
Section: Socio-economic Segregation In Lithuaniamentioning
confidence: 99%
“…nesaugumas, socialinė poliarizacija ir dezintegracija kontekste, pradėtas vadinti "naujuoju skurdu" (Tereškinas, Bučaitė-Vilkė, 2015). Neabejotina, kad visos skurdo dimensijos tarpusavyje siejasi ir formuoja vis kitokias jo raiškas, tačiau skirtingi skurdo šaltiniai gali sąlygoti įvairias individų gyveno patirtis, dėl to svarbu kalbėti ne tik apie materialinį skurdą, kuris daugiausia apibrėžia vargingiausius (pajamų ir turto prasme) visuomenės sluoksnius, bet ir apie kitokių rūšių skurdo kilmę, siekiant suprasti, kaip ši skurdo forma vienaip arba kitaip paliečia ir vidutines arba didesnes pajamas turinčius gyventojus ir atitinkamai formuoja jų santykį su gyvenamuoju laiku, informacija, visuomene, galimybėmis, ateities perspektyvomis ir kokias kasdienio gyvenimo prasmes leidžia konstruoti.…”
unclassified